BREEDING PRACTICES IN DAIRY ANIMALS OF RURAL AREA UNDER MILK SHED OF NORTH GUJARAT - Modi , R J; Patel , N B (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
A survey work on breeding practices followed in dairy animals of rural area in Sabarkantha district of North Gujarat was carried out. One hundred respondents of 10 villages having elite dairy animals were included in the study. Data revealed that 100 per cent farmers observed only mucus discharge and bellowing as a sole symptom of heat detection. Almost all farmers used AI for breeding their crossbred cows, while for buffaloes 13.00 and 5.00 per cent farmers followed AI and nature breeding, respectively, and the remaining 82.00 per cent farmers opted for both A.I. and NS. The AI/NS was followed between 12 and 24 hours after heat detection by all the respondents. Results revealed that majority of cows (82.18%) and buffaloes (90.00%) had = 15 months and 18 months of calving intervals, respectively. Poor result of AI (16.00%) and higher incidence of repeat breeding (22.00%) in buffaloes were the main constraints faced by the farmers. Better awareness of farmers regarding breeding of dairy animals was observed due to co-operative system in the district.
Keywords: Breeding practices; Rural area; Dairy animals